CSR Case Studies: Identifying Core References with Direct Citation Analysis - Lis, Andrzej (Journal of Corporate Responsibility and Leadership, 2020)
Purpose: The aim of the paper is to identify, through citation analysis, the core references employing case study methodology to explore CSR issues in various organizational contexts. The research process is focused on the following study questions: (1) What are the core references analysing CSR case studies? (2) What are the research contexts of the top rated case studies in CSR? Methodology: The study employs the method of direct citation analysis, which is categorized among the science mapping, bibliometric methods. As the method of citation analysis favours older publications, which have had more opportunities to receive a higher number of citations, the traditional approach based on identifying the most cited publications is supplemented with the analysis of the normalized number of citations, which mitigates such a bias. The analysis and visualization of findings are supported with VOSviewer software. Findings: The analysis has identified the core references among case studies exploring corporate social responsibility issues. Then, the identified publications have been explored and their research contexts have been recognized.The core case studies in CSR show their particular interest in such contexts and issues as: (1) heavy industries (e.g. mining and oil industries); (2) supply chains; (3) various types of businesses, including large companies, SMEs, and family businesses; (4) the perspectives of important stakeholders such as governments and NGOs; and recently (5) the food industry. Research and practical implications: Through mapping scientific output of CSR case studies, the paper contributes first and foremost to the development of management theory. It points out the most recognized publications, to be considered as role models for the followers. It may also provide inspiration for further exploration of corporate social responsibility practices with the use of case study methodology. Originality/value: The uniqueness of the paper derives from the fact that CSR case studies have not been yet mapped as a research field. Moreover, the employment of bibliometric methodology enabling objective analysis of a large number of publications and their attributes, and effective visualization techniques increase value of the study. Paper type: Review.